The feasibility of macro alga E.spinosum for colour removal from real textile wastewater - Nadiah, Mokhtar; F. A., Aziz; Edriyana, Abd Aziz; Hasmanie, Abdul Halim; A., Aris (IOP Publishing, 2020)
Industrial textile wastewater usually contains high chemical substances, suspended solids and a very conspicuous intense colour. The complexity of textile wastewater had urged for an effective treatment method. This paper studies the feasibility of red macro alga, Euchema Spinosum as a natural and low-cost biosorbent for the removal of colour in real textile wastewater. The characterization of aforesaid biosorbent was analysed for its physical and chemical properties using Brunauer-Emmett-Teller (BET) and X-ray Fluorescence Spectrometer (XRF). The effect of dosage and contact time on colour removal was analysed using batch biosorption experiments. The BET result confirmed that surface area of biosorbent is relatively small suitable for biosorbent characteristic. The result shows that at optimum dosage of 15g/L within 48 hours, E. spinosum was able to remove 93.71% of colour from textile wastewater. Therefore, E. spinosum was found to be highly effective in treating real textile.